COMMUNICATION PROGRAM PLANNING STUDY: THE EFFECT OF THE USE OF CHATGPT ON EDUCATION TO ENCOURAGE RESPONSIBLE AND ETHICAL LIFELONG LEARNING - Putri Syahrani (ZILLZELL MEDIA PRIMA, 2024)
Technology, which continues to develop along with the advancement of science, plays a key role in improving the understanding of science in education. Artificial intelligence (AI) is playing a key role in the transformation of education, and ChatGPT, as a generative language model, opens up new opportunities for innovative learning experiences. The determination of strategies in communication planning is always related to the elements of communication. The purpose of this study is to find out how the role of Communication Program Planning Studies has the Influence of the Use of ChatGPT on Education to Encourage Responsible and Ethical Lifelong Learning. The research method uses a descriptive qualitative method. The data used is secondary data, the researcher uses 16 articles and appropriate books as a reference in writing scientific papers. The results of this study show that the presence of ChatGPT is the result of the implementation of communication program planning that has received a positive response from various circles, namely students, students, and educators.